Response of Growth and Production of Shallot (Allium ascalonicum L.) to Liquid Fertilizer and Cattle Manure - Ifan Aulia Candra; Lisdayani Lisdayani; Eri Samah (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2023)
The purpose of this research is to improve the physical properties and fertility of soil to improve production of shallot. The research method used is a randomized block factorial design with 3 replication. The first factor was application of liquid fertilizer (N) consisting of 3 levels (N0: 0 cm3/L  water; N1: 1.5 cm3/L  water; N2: 3 cm3/L water). Second factor was cattle manure (A) consisting of 4 levels, namely: A0: 0 g; A1: 40 g cattle manure; A2: 80 g cattle manure; and A3: 120 g cattle manure. The results shown treatment with liquid fertilizer has a significant effect on plant height at weeks after planting (WAP). The study showed that treatment with liquid fertilizer has a significant effect on plant height, tuber weight per clump, and tuber weight per plot, but didn’t not have a significant effect on number of leaves and number of samplings of the shallot plants. Treatment with cattle manure has a significant effect on plant height, tuber weight per clump, tuber weight per plot, and tuber diameter, but does not have a significant effect on number of leaves and number of saplings of the shallot plants. It can be concluded that the higher the application of liquid fertilizer, up to 3 cm3/L , the higher the growth and production of shallot plants, and the higher the application of cattle manure, up to 120 g/plot the higher the growth and production of shallot plants. Keywords:  Plant height, Shallot, Soil Fertility, Tuber weight, Tuber size.